VISTA immune checkpoint blunts radiotherapy-induced antitumor immune response - Dhanya K. Nambiar; Sainiteesh Maddineni; Jimpi Langthasa; Hongbin Cao; Vignesh Viswanathan; Junyan Liu; Md Tauhidul Islam; Nishant Mehta; Jessica Frank; Alexander Real; Tia Cheunkarndee; Eyiwunmi Eghonghon Laseinde; et al. (Cell Reports, 2025)
Summary: Radiotherapy (RT) is a key treatment for solid neoplasms like head and neck cancer (HNC), but it can also activate and recruit immunosuppressive myeloid cells, causing treatment failure. In this study, we examine the role of V-domain immunoglobulin suppressor of T cell activation (VISTA) on myeloid cells during RT. We discovered high VISTA expression on myeloid cells in the tumor microenvironment (TME) of both murine and human HNC, with RT increasing VISTA+ myeloid cells in the TME and circulation. Compared to VISTA+/+ mice, VISTA−/− mice showed improved tumor control with RT, with their macrophages and neutrophils exhibiting antitumorigenic properties on sc-RNA-seq analysis, especially with RT. Combining anti-VISTA antibodies (active or silent Fc) with RT (fractionated or ablative) significantly decreased tumor volume compared to either treatment alone in multiple preclinical models (HNC, breast cancer, and colorectal cancer), enhancing systemic antitumor immune response with augmented intra-tumoral T cell function through myeloid repolarization. Targeting VISTA could improve the efficacy of RT.